Impact Assessment of FLDs on Paddy in North Eastern Himalayan Region - Pandey, Nitin Kumar; Indu, (Indian Journal of Extension Education, 2017)
Rice is an important staple food for more than half of the global population. Krishi Vigyan Kendra Tawang, conducted  demonstrations on paddy from 2011- 14 for improvement of paddy production in Tawang district of Arunachal pradesh.  An impact evaluation was based on the comparison of participant and non-participant farmers with reference to increase  in knowledge level and adoption of participant farmers of improved practices of paddy production. FLDs were carried out  in a systematic manner on farmers fields to show the worth of HYV in comparison to local varieties and there by  convincing farmers about potentialities of improved practices. The highest yield12 q/ ha was recorded in the year of 2011- 14 in the FLDs, which was 40 per cent more over the farmers practices. The gross returns (` 19200/ha) and net returns (`6200/ha) with higher cost benefit ratio 1.5:1 compared to 1.2: 1 of non-participant, FLDs programme to improve overall  knowledge and adoption amongst the farmers in the region to boost paddy production.
Keywords: Impact assessment; improved practices; participant; paddy; region